“Silence is Golden:” Explaining the Silent Majority Based on Fatalism, Culture, and National Attachments - Mashuri, Ali; Nurmala, Sukma; Zaduqisti, Esti (UI Scholars Hub, 2025)
Why do citizens tend to be silent about a country’s social, political, or economic problems? The silent majority refers to most members of society not support or engage in collective action to protest injustice. This study aimed to explain the silent majority’s psychosocial dynamics and fill the research gaps in the psychology literature that focuses on collective action and its determining factors. The study’s participants (N = 349), recruited using convenience sampling, were undergraduate and graduate students from several universities in Indonesia. In our study, the psychosocial characteristics of the silent majority included fatalism, cultural dimensions (i.e., power distance, uncertainty avoidance, collectivism, and masculinity), and national attachments (i.e., national identification and nationalism). Fatalism was the most significant predictor of the silent majority, with substantial mediating effects on the role of cultural dimensions in strengthening the silent majority. The findings revealed that nationalism significantly moderated the relationship between fatalism and the silent majority. Specifically, the positive relationship between fatalism and the silent majority was significantly stronger among participants with high, rather than low, levels of nationalism. These observations imply that fatalistic beliefs, the cultural characteristics of society’s members, and national pride underlie the psychosocial dynamics of the silent majority.